NF-κβ: A Potential Target in the Management of Vascular Complications of Diabetes - Suryavanshi, Sachin V.; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2017)
Diabetes is a metabolic disorder affecting large percentage of population worldwide. NF-κβ plays key role in pathogenesis of vascular complications of diabetes. Persistent hyperglycemia activates NF-κβ that triggers expression of various cytokines, chemokines and cell adhesion molecules. Over-expression of TNF-α, interleukins, TGF-β, Bcl2 and other pro-inflammatory proteins and pro-apoptotic genes by NF-κβ is key risk factor in vascular dysfunction. NF-κβ over-expression also triggers calcification of endothelial cells leading to endothelial dysfunction and further vascular complications. Inhibition of NF-κβ pro-inflammatory pathway is upcoming novel target for management of vascular complications of diabetes. Various natural and synthetic inhibitors of NF-κβ have been studied in management of diabetic complications. Recent preclinical and clinical studies validate NF-κβ as promising target in the management of vascular complications of diabetes.